Economic analysis for ecosystem assessments: Application for the UK National Ecosystem Assessment (NEA) - Ian Bateman (University of East Anglia, The Centre for Social and Economic Research on the Global Environment (CSERGE), 2009)
The paper considers methodological issues pertinent to the economic assessment of ecosystem services. It is primarily written for a natural science audience however it also proposes a methodology which is intended to be of interest to economists charged with undertaking valuation work for ecosystem service assessments. The first part of the report introduces the concepts underpinning the economic approach towards the assessment and valuation of ecosystem services. The second part considers the particular issues arising for the economic analysis of findings from the UK National Ecosystem Assessment (NEA). Annexes to the paper use a case study approach to illustrate particular issues. The first concerns potential conversions from agriculture into multi-purpose woodland and illustrates the quantification and valuation of land use change. The application of geographical information system (GIS) routines allows spatial complexity to be incorporated within the analysis. Key concepts are illustrated such as making allowance for subsidies, the marginal value concept, and the valuation of non-market externalities (such as carbon storage of open-access recreation). The case study also shows that, if issues such as spatial variation and externalities are ignored then sole reliance upon market prices can lead to perverse outcomes which are actually to the detriment of society. This spatial focus is extended in a second annex to consider issues arising in the aggregation of values. A third annex reproduces a short questionnaire send to natural scientists working on the NEA intended to help identify the goods which will be the focus of the economic analysis.
Keywords: 330; Umweltschutz; Umweltpolitik; Wohlfahrtseffekt; Bewertung; Großbritannien